2017
DOI: 10.1016/j.bbamcr.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Signal peptide peptidase and SPP-like proteases - Possible therapeutic targets?

Abstract: Signal peptide peptidase (SPP) and the four homologous SPP-like proteases SPPL2a, SPPL2b, SPPL2c and SPPL3 are GxGD-type intramembrane-cleaving proteases (I-CLIPs). In addition to divergent subcellular localisations, distinct differences in the mechanistic properties and substrate requirements of individual family members have been unravelled. SPP/SPPL proteases employ a catalytic mechanism related to that of the γ-secretase complex. Nevertheless, differential targeting of SPP/SPPL proteases and γ-secretase by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 162 publications
(330 reference statements)
2
28
0
Order By: Relevance
“…Similar to our results, an extensive study of the human proteome identified SPPL2c only in testis [38]. Based on the published phenotypes of SPPL2a/b-and SPPL3-deficient mice, these proteases play a significant role in the immune system [7]. In this regard, the newly described role of SPPL2c extends the in vivo relevance of SPP/SPPL to the reproductive system.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to our results, an extensive study of the human proteome identified SPPL2c only in testis [38]. Based on the published phenotypes of SPPL2a/b-and SPPL3-deficient mice, these proteases play a significant role in the immune system [7]. In this regard, the newly described role of SPPL2c extends the in vivo relevance of SPP/SPPL to the reproductive system.…”
Section: Discussionsupporting
confidence: 88%
“…The inhibitory profile of SPPL2c indicates two remarkable differences with regard to other SPP/SPPL proteases. In the performed RAMP4-2 cleavage assay, SPPL2c was not inhibited by the active site inhibitor (Z-LL) 2 -ketone, which acts on all SPP/SPPL proteases with the exception of SPPL3 [4,7,25,28]. In contrast, the c-secretase inhibitor DAPT partially blocked cleavage by SPPL2c.…”
Section: Discussionmentioning
confidence: 92%
“…Signal peptide peptidases (SPPs) and the related signal peptide peptidase‐like (SPPL) proteases are a family of GxGD‐type intramembrane aspartyl proteases that were identified in search of homologs to presenilin, the catalytically active subunit of gamma secretase. These polytopic membrane proteins are known to cleave Type II (N in ) and Type IV tail‐anchored proteins.…”
Section: Distinct Intramembrane Proteases Are Located In the Er (Spp mentioning
confidence: 99%
“…As recently reviewed [13], SPP plays a role in different viral infections by being involved in the processing and thereby maturation of different viral proteins. By this means, the SPP activity of the host cell is a critical factor for viral replication.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…This process significantly profited from existing compounds initially generated for inhibition of the related γ-secretase for treatment of Alzheimer's disease and leukaemia [113]. While some of these inhibitors appear to selectively target γ-secretase and spare the SPP/SPPL family, others like L-685,458 and LY-411575 also inhibit processing of SPP/SPPL substrates even though with different efficiency for individual proteases [13,114,115]. In this context, it was an interesting observation that SPPL2c activity is targeted by DAPT [18], a well-established γ-secretase inhibitor (GSI) that spares all other SPP/SPPL proteases [13] strongly arguing for major differences between SPPL2c and the other family members.…”
Section: Recent Advances In Spp/sppl Inhibitor Developmentmentioning
confidence: 99%